Topology optimization and high cycle fatigue modeling in additively manufactured dental implants (Transactions on Additive Manufacturing Meets Medicine, 2024)
We introduce an innovative and efficient methodology for improving the longevity and performance of dental implants while minimizing stress-shielding. By modifying the internal structure of the implant, two distinct strategies—topology optimization [1] and TPMS lattices—are employed to enhance implant design. These strategies are analyzed using an ANSYS model with material parameters from mechanical tests of additively manufactured Ti-6Al-4V. Topology optimized structures show a reduction in stress shielding compared to standard solid implants.Additionally, we presents a novel and efficient methodology based on the Hamilton principle [2,3] for modeling fatigue induced by damage and plasticity, focusing on speed and robustness. Traditional cycle-by-cycle simulations are inefficient for high-cycle fatigue due to excessive processing time. To overcome this, the proposed approach simulates the amplitude of the displacement load, bypassing the need for cycle-by-cycle analysis. This method allows for the simulation of force reactions over time within a changing time space, enabling the simple extraction of hysteresis loops and S-N curves during postprocessing without loss of accuracy. The long-term stability of the implants is further investigated using a high-cycle fatigue material model, revealing no fatigue in the selected topology optimized structures.Acknowledgments: DFG FOR5250, Project number: 449916462, TP-Z: Mechanism-based characterization and modeling of permanent and bioresorbable implants with tailored functionality based on innovative in vivo, in vitro and in silico methods. TP-7: In silico design of implants based on a multiscale approachReferences[1]  Kick, M., Junker, P., Thermodynamic topology optimization for hardening materials, arXiv preprint arXiv:2103.03567, (2024).[2]  Philipp Junker, Stephan Schwarz, Dustin R. Jantos, and Klaus Hackl. A fast and robust numerical treatment of a gradient enhanced model for brittle damage. International Journal for Multiscale Computational Engineering, 17(2):151–180, 2019.[3] Junker, P., Balzani, D.  An extended Hamilton principle as unifying theory for coupled problems and dissipative microstructure evolution. Continuum Mech. Thermodyn. 33, 1931–1956 (2021). https://doi.org/10.1007/s00161-021-01017-z.
Keywords: Dental Implant; Titanium alloy; stress shielding